Milk fat globule epidermal growth factor-factor 8-derived peptide attenuates organ injury and improves survival in sepsis - Yang, Weng-Lang (Crit Care, 2015)
INTRODUCTION: Sepsis involves overwhelming inflammatory responses with subsequent immune-suppression that can lead to multiple organ dysfunction and ultimately death. Milk fat globule epidermal growth factor-factor 8 (MFG-E8) is a secretory protein found to have multiple biological activities against autoimmune and inflammatory diseases. MFG-E8 contains an Arg-Gly-Asp (RGD) motif involved in cell-cell and cell-matrix interactions. In sepsis, excessive neutrophils migration through endothelial cells and matrix to sites of inflammation results in organ damage. We hypothesized that MFG-E8-derived short peptides (MSP) flanking its RGD motif could provide protection against organ injury in sepsis. METHODS: The differentiated human neutrophil-like HL-60 cells (dHL60) were incubated with a series of peptides flanking the RGD motif of human MFG-E8 for a cell adhesion assay to fibronectin or human pulmonary artery endothelial cells (PAECs). For the induction of sepsis, male C57BL/6 mice (20–25 g) were subjected to cecal ligation and puncture (CLP). Peptide MSP68 (1 mg/kg body weight) or normal saline (vehicle) was injected intravenously at 2 h after CLP. Blood and tissue samples were collected at 20 h after CLP for various measurements. RESULTS: After screening, peptide MSP68 (VRGDV) had the highest inhibition of dHL-60 cell adhesion to fibronectin by 55.8 % and to PAEC by 67.7 %. MSP68 treatment significantly decreased plasma levels of organ injury marker AST by 37.1 % and the proinflammatory cytokines IL-6 and TNF-α by 61.9 % and 22.1 %, respectively after CLP. MSP68 improved the integrity of microscopic architectures, decreased IL-6 levels in the lungs by 85.1 %, and reduced apoptosis. MSP68 treatment also significantly reduced the total number of neutrophil infiltration by 61.9 % and 48.3 % as well as MPO activity by 40.8 % and 47.3 % in the lungs and liver, respectively, after CLP. Moreover, the number of bacteria translocated to mesenteric lymph nodes was decreased by 57 % with MSP68 treatment. Finally, the 10-day survival rate was increased from 26 % in the vehicle group to 58 % in the MSP68-treated group. CONCLUSIONS: MSP68 effectively inhibits excessive neutrophils infiltrating to organs, leading to moderate attenuation of organ injury and significantly improved survival in septic mice. Thus, MSP68 may be a potential therapeutic agent for treating sepsis.